Guidance on Evaluation Inception Reports - CGIAR Independent Evaluation Arrangement (CGIAR Independent Evaluation Arrangement, 2015)
This document provides guidance on how to develop an evaluation Inception Report and its core contents, namely the evaluation purpose, focus, design and conduct.